The term (كلمة) in the Holy Quran Between Translation and interpretation - Abdulhakeem Abdullah, Jamal (Al-Adab Journal, 2021)
There is no doubt that the correct and accurate translation of religious terms and concepts is of the utmost importance for those who seek to be precise in their translations and strive to convey the meanings to the readers of the language transmitted with extreme precision. and linguistic proficiency, taking into account the linguistic and cultural stock of the transmitted language, as this is a major condition for its successful Translation. This research seeks to highlight the rhetoric of the Koran by touching on the polysemy of a term in the translation. In this research, the term "word" is treated because it is mentioned in 22 verses in different surahs of the Quran. After clarifying what translation and interpretation are, we give an overview of the history of Quran translation and mention the first to translate the Quran into French and identify the three corpuses on which the research depends (translations of the Quran in French). In order to obtain the exact result of these translations, two versions of the interpretations of these verses are consulted. To clearly show the results of this research are represented in tabular and graphical form. The conclusion of the research which was reached is that the use by the translator of the Quran interpretation books of the Quranic verses is very necessary in order to follow the rhetoric of the Quran and get an accurate translation. In conclusion, it is hoped that this simple research will help support research efforts on translation in general and Quran translation in particular.